Differential Equation Model of the LLC Resonant Converter in the Ideal Case - Fang Li; Haodong Lei; Ruixiang Hao; Siwei Liu; Xiaojie You; Jingmin Gao (Energies, 2020)
The LLC resonant converter has been widely used in direct current (DC) power supply applications. However, fundamental harmonic approximation or other simplified analyses will introduce inevitable deviations. Therefore, the differential equation model with numerical solution of the LLC converter is proposed in this paper based on the operational principle of the ideal case. In order to solve the differential equation, initial values need to be substituted. The accurate LLC model based on time interval analysis is very complicated and cannot be used. In this paper, solution methods of the initial values corresponding to different switching frequencies are proposed. The initial values can be solved conveniently. Furthermore, the voltage gain curve is modified by the idealized analysis. Lastly, all the above research is verified by PSIM simulation. The work is helpful to understand the operational principle of the LLC resonant converter.